An Empirical Study on the Influence of Financial Literacy on Personal Financial Management among University Students in Indonesia - Putri Ratnasari; Rizka Aisyah Nurjannah; Yulianti Karoma (SEULANGA SYSTEM PUBLISHER, 2025)
This study aims to analyze the impact of financial literacy on personal financial management among university students in Indonesia. Additionally, this study explores the role of digital technology usage in enhancing students' personal financial management. Using a quantitative descriptive approach, data was collected through a survey distributed to students from various universities in Indonesia. The results indicate that financial literacy significantly influences students' personal financial management. Students with higher financial literacy are more likely to manage their budgets effectively, save regularly, and avoid excessive debt. Furthermore, the use of digital technology such as mobile banking apps and digital wallets has been shown to improve students' personal financial management by making it easier for them to track expenses and monitor budgets in real-time. However, demographic factors such as gender and age did not show a significant effect on students' personal financial management in this study. The findings suggest that increasing financial literacy and utilizing digital technology can enhance students' personal financial management. Therefore, it is crucial for universities and policymakers to design more effective educational programs on financial literacy and digital technology so that students can better manage their finances. This research provides valuable insights for the development of financial education curricula that are relevant to the financial challenges faced by students in the digital age.